2004
DOI: 10.1016/s0896-6273(04)00046-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional Topography of Corticothalamic Feedback Enhances Thalamic Spatial Response Tuning in the Somatosensory Whisker/Barrel System

Abstract: Corticothalamic (CT) projections are approximately 10 times more numerous than thalamocortical projections, yet their function in sensory processing is poorly understood. In particular, the functional significance of the topographic precision of CT feedback is unknown. We addressed these issues in the rodent somatosensory whisker/barrel system by deflecting individual whiskers and pharmacologically enhancing activity in layer VI of single whisker-related cortical columns. Enhancement of corticothalamic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 56 publications
8
137
1
Order By: Relevance
“…However, the spatially diffuse acetylcholine action of brainstem inputs which activates slow muscarinic receptors in the VPM may represent the overall level of vigilance and modulate the thalamus globally on slow time scales. In contrast, spatially and temporally precise changes in firing mode and adaptation likely are under L6 control because of the topographical precision of cortico-thalamic axons (40,41). These results somewhat contrast with a study by Olsen et al (23) in the visual thalamus in which tonic mode shifts by L6 were observed but did not reach significance level (SI Discussion).…”
Section: Discussionmentioning
confidence: 57%
“…However, the spatially diffuse acetylcholine action of brainstem inputs which activates slow muscarinic receptors in the VPM may represent the overall level of vigilance and modulate the thalamus globally on slow time scales. In contrast, spatially and temporally precise changes in firing mode and adaptation likely are under L6 control because of the topographical precision of cortico-thalamic axons (40,41). These results somewhat contrast with a study by Olsen et al (23) in the visual thalamus in which tonic mode shifts by L6 were observed but did not reach significance level (SI Discussion).…”
Section: Discussionmentioning
confidence: 57%
“…Similar mechanisms have been suggested to operate in both the somatosensory [57][58][59][60] and the auditory [5] systems.…”
Section: Functional Aspects Of Thalamocortical Interactionsmentioning
confidence: 55%
“…A recent study has further reported that activation of the barrel column enhances the sensory responses of relay neurons in the corresponding thalamic compartment, or barreloid (Temereanca and Simons, 2004). L6 CTN activation in a barrel column thus has an excitatory/ facilitatory influence on the activity of thalamic relay neurons, which transfer peripheral information to the cerebral cortex.…”
Section: Discussionmentioning
confidence: 90%
“…In this reciprocal circuit, L6 corticothalamic projection neurons (CTNs) are considered to enhance and tune thalamic responses to peripheral stimuli (Yuan et al, 1986;Yan and Suga, 1996;Przybyszewski et al, 2000;Alitto and Usrey, 2003;Temereanca and Simons, 2004;Thomson, 2010). Local connections between cortical layers are well developed (Briggs and Callaway, 2001;Mercer et al, 2005;Zarrinpar and Callaway, 2006;West et al, 2006;Lefort et al, 2009;Llano and Sherman, 2009;Lam and Sherman, 2010;Hooks et al, 2011), and in addition to external inputs, local translaminar inputs are involved in shaping CTN activity.…”
Section: Introductionmentioning
confidence: 99%